Near extinction of the HBV quasispecies driven by the hard selective sweep in chronic hepatitis B - Daiqiang Lu; Andong He; Guichan Liao; Renyu Zhou; Zichun Cheng; Ka Cheuk Yip; Xiufang Wang; Wei Cao; Jiaojiao Peng; Ruiman Li; Jie Peng; Feng Gao (mBio)
ABSTRACT The viral quasispecies play an important role in pathogenesis. However, little is known about the nature of hepatitis B virus (HBV) quasispecies and its impact on the outcomes of chronic hepatitis B. Here, we characterized the bona fide quasispecies viral populations from 16 chronically infected patients by analyzing the near full-length viral genomes obtained by single genome sequencing. Follow-up plasma samples were collected from six patients after 6 months and from four patients after 3–5 years. We found that the viral population diversity levels were highly variable among these patients, depending on the status of the selection pressure. To further understand the host selection pressure over time, we compared viral sequences from different timepoints in 10 patients and found the hard selective sweep (HSS) at the whole genome level in three of them. This HSS was extremely strong and drove the highly diversified viral quasispecies into a distinct yet homogeneous viral population in each patient after 1–4 years of infection. The identical or nearly identical sequences in the homogeneous viral population indicate that they originate from a single infected source. Predominant and fixed mutations were observed in well-characterized T cell epitopes but not in known epitopes of neutralizing antibodies or N-linked glycosylation sites. Since HSS is strong enough to drive HBV quasispecies into near extinction and frequently occurs in chronic hepatitis B patients, this raises the hope for eliminating HBV from the last single reservoir through enhancing specific T cell immune responses targeting the highly selected homogeneous viruses.IMPORTANCEThe nature of bona fide hepatitis B virus (HBV) quasispecies and its potential impact on the outcomes of chronic hepatitis B are not well understood. Analysis of the high-quality near full-length HBV sequences from chronic hepatitis B patients identifies the strong hard selective sweep that can drive the viral quasispecies into a distinct yet highly homogeneous viral population. The nearly identical viral population suggests that all these viruses are from a single source. Predominant mutations were identified in known T cell epitopes but not in epitopes for neutralizing antibodies, indicating that the hard selective sweep is most likely driven by T cell selection pressure. These findings indicate that enhancement of specific T cell responses during chronic hepatitis B can easily eliminate the highly homogeneous viral population and serve as a promising approach to achieve the goal of a functional cure for chronic hepatitis B.